2022
DOI: 10.1155/2022/3450672
|View full text |Cite|
|
Sign up to set email alerts
|

ECM-Mimicking Hydrogels Loaded with Bone Mesenchymal Stem Cell-Derived Exosomes for the Treatment of Cartilage Defects

Abstract: It is well-established that treating articular cartilage injuries is clinically challenging since they lack blood arteries, nerves, and lymphoid tissue. Recent studies have revealed that bone marrow stem cell-derived exosomes (BMSCs-Exos) exert significant chondroprotective effects through paracrine secretions, and hydrogel-based materials can synergize the exosomes through sustained release. Therefore, this research aims to synthesize an ECM (extracellular matrix)-mimicking gelatin methacryloyl (GelMA) hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Among the promising candidates are serum CTX-II and COMP. Type II collagen and aggrecan represent the most characteristic proteins in the cartilage matrix [ 48 , 49 ]; particularly, type II collagen represents 80–90% of the collagen in cartilage tissue. MMPs are the main players in the degradation of type II collagen as a hallmark of irreversible cartilage damage [ 15 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the promising candidates are serum CTX-II and COMP. Type II collagen and aggrecan represent the most characteristic proteins in the cartilage matrix [ 48 , 49 ]; particularly, type II collagen represents 80–90% of the collagen in cartilage tissue. MMPs are the main players in the degradation of type II collagen as a hallmark of irreversible cartilage damage [ 15 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The curing point of 5% GelMA hydrogel with 0.5% Irgacure 2959 was found to be ∼100 s, and ∼20 s when photocured using 5 and 30 mW/cm 2 UV (λ = 365 nm) UV intensity, respectively . Most 3D bioprinters work with an ideal UV illumination between 0 and 30 mW/cm 2 , , while the most common intensity is 6.9 mW/cm 2 . ,,, Irgacure 2959 and LAP are the most common type I photoinitiators used for GelMA curing because of their water solubility, good curing efficiency, and acceptable cytotoxicity. The solubility of LAP is comparatively much higher (8.5%) compared to that of Irgacure 2959 (∼0.5%) .…”
Section: Structure Stability and Properties Of Gelma Biomaterials Inksmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%